Building Statistical Capacity in Fragile and Conflict-Affected States - Medina Cas, Stephanie; Alem, Yasmin; Shirakawa, Jacinta Bernadette (Washington, D.C. : International Monetary Fund, 2022)
Based on internal data, this paper finds that the capacity development program of the IMF's Statistics Department has prioritized technical assistance and training to fragile and conflict-affected states. These interventions have yielded only slightly weaker results in fragile states than in other states. However, capacity development is constantly needed to make up for the dissipation of progress resulting from insufficient resources that fragile and conflict-affected states allocate to the statistical function, inadequate inter-agency coordination, and the pervasive impact of shocks exogenous to the statistical system. Greater coordination with other capacity development providers and within the IMF can help partially overcome low absorptive capacity in fragile states. Statistical capacity development is more effective when it is tailored to countries' level of fragility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Capacity Development, Statistics, Data and Fragile States; Development Planning and Policy; Government Finance Statistics Manual; STA CD Delivery; STA CD Mission